2019
DOI: 10.1097/icb.0000000000000548
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features in a Case of Occult Macular Dystrophy With Rp1l1 Mutation

Abstract: Spectral domain optical coherence tomography and multifocal electroretinography can serve as diagnostic testings for patients with OMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Occult macular dystrophy (OMD; OMIM:613587), first described by Miyake et al in 1989 [1-5], is the most prevalent form of macular dystrophy in the East Asian population [6][7][8][9][10][11][12][13][14][15][16]. This non-syndromic autosomal dominant (AD) disorder is characterised by progressive loss of visual acuity (VA) in both eyes despite the essentially normal fundus appearance and normal full-field electroretinogram (ffERG) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occult macular dystrophy (OMD; OMIM:613587), first described by Miyake et al in 1989 [1-5], is the most prevalent form of macular dystrophy in the East Asian population [6][7][8][9][10][11][12][13][14][15][16]. This non-syndromic autosomal dominant (AD) disorder is characterised by progressive loss of visual acuity (VA) in both eyes despite the essentially normal fundus appearance and normal full-field electroretinogram (ffERG) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The immunohistochemistry assessment in monkeys demonstrated the expression of the RP1L1 protein in rod/cone photoreceptor cells, suggesting its role in morphological and functional maintenance [33]. Consequently, many RP1L1 variants have been reported in families with AD-OMD [6,10,11,14,15,19,34,35]. Since the identifying of biallelic sequence variants illustrating the loss of function in patients with retinitis pigmentosa (RP) in 2013, RP1L1 variants in an autosomal recessive (AR) manner have also been reported [12,19,30,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…10,13,14 To date, numerous studies describing OMD patients with RP1L1 mutations have been reported, but limited data are available for the Chinese population. 4,15,16 Thus, this study aims to investigate the clinical and genetic characteristics of a small cohort of Chinese OMD patients.…”
mentioning
confidence: 99%